Mechanisms of tumour cell escape encountered in treating lymphocytic leukaemia with anti-idiotypic antibody. - Gordon, J. (Nature Publishing Group, 1984)
Four patients with chronic lymphocytic leukaemia were treated by one or more infusions of polyclonal antibody specific for the immunoglobulin idiotype expressed on their leukaemic cells. The antibody was in the form of IgG from sheep antiserum. Three of the 4 cases showed a significant fall in blood lymphocyte count. On one occasion most of the residual circulating lymphocytes were apparently dead. However on all occasions the cell counts rebounded to near pre-infusion levels within one week. Viable lymphocytes recovered from the blood after infusion always showed evidence of antigenic modulation: a diminished level of surface idiotype in a patched distribution, with an accompanying refractoriness to lysis by anti-idiotype plus complement. When cultured in vitro blood lymphocytes from three of the four patients revealed an appreciable export of idiotypic Ig. These 3 patients showed plasma levels of idiotypic Ig up to 400 micrograms ml-1, reduced by plasma exchange prior to infusion. The fourth patient had a level of less than 4 micrograms ml-1, and was the only one in whom free antibody could be found in the plasma after infusion. These cases demonstrate two major factors which thwart antibody attack on leukaemic cells--extracellular antigen and antigenic modulation--as well as problems relating to sparseness of surface antigen, recruitment of effectors, and exhaustion of effectors.